Natural history of gastroesophageal reflux in infancy: new data from a prospective cohort - Marlène Curien-Chotard; Prévost Jantchou (BMC Pediatrics, 2020)
Abstract Background Gastroesophageal reflux (GER) is common in infants. Gastroesophageal reflux disease (GERD) is defined as GER leading to troublesome symptoms that affect daily functioning and/or complications. This study is aimed at determining the prevalence and progression of GER and GERD in a cohort of healthy term infants from birth to 12 months old. Methods We conducted a prospective cohort study including all full-term living neonates born at Besançon Teaching Hospital, France. Parents completed a clinical report form and the Infant Gastroesophageal Reflux Questionnaire-Revised (I-GERQ-R) at 1, 3, 6, 10, and 12 months of age. GER was defined as score ≥ 1 to the first question with I-GERQ-R score < 16, and GERD as score ≥ 1 to the first question with I-GERQ-R score ≥ 16. Regurgitation was based on the answer to the first question of the I-GERQ-R as anything coming out of the mouth daily. Results 157/347 births were included (83 boys). The prevalence of regurgitation at least once a day was 45.7% overall. In total: 72, 69, 56, 18, and 13% of infants regurgitated at least once a day at 1, 3, 6, 10, and 12 months of age, respectively. Physiological GER affected 53, 59, 51, 16, and 12% of infants; GERD, 19, 9, 5, 2, and 2%, respectively. Two risk factors were identified: family history of GER and exposure to passive smoking. Treatment included dietary modification (14%) and pharmacotherapy (5%). Conclusion Physiological GER peaked at 3 months, GERD at 1 month. Most cases resolved on their own. GER and GERD are very common in the infant’s population and parents should be reassured/educated regarding symptoms, warning signs, and generally favorable prognosis. I-GERQ-R is useful to the clinical screening and follow up for GER and GERD.